IMPLEMENTASI E-AUDIT DALAM MENINGKATKAN FUNGSI PEMERIKSAAN PENGELOLAAN DAN PERTANGGUNGJAWABAN KEUANGAN NEGARA PADA BPK-RI - Pradita, Alvita (Jurnal Akuntansi AKUNESA, 2014)
Financial examination process of Badan Pemeriksa Keuangan (BPK) takes too much time. At the same time, the BPK is required to report the results of the examination or accountability immediately. Therefore, BPK is seeking to improve the quality of examination of financial management and accountability of the state through e-audit system. This paper explains how e-audit synergy mechanism and benefits of the implementation of e-audit on the financial management and barriers in implementing e-audit based on literature studies. E-audit is a monitoring process through the BPK data center by combining existing electronic data on BPK with auditee electronic data. Thus, the BPK will be able to run the recording, processing, exchange, and use of monitoring data from various parties, in order to carry out inspection tasks for the management and accountability of state finance electronically. Keywords: e-audit, financial examination, financial management, accountability, sinergy e-audit.